Adaptation, Access to Resources and Mobility: From Contemporary Pastoral Systems to Ancient Societies. (1st January 2017) - Salpeteur, M.; Madella, M.; Patel, H.R.; Reyes-García, V.
Abstract : Building on the literature on adaptation and on examples from contemporary pastoralists in Gujarat, we explore dynamics of pastoral systems and, more precisely, their adaptive strategies. We specifically focus on resource accessibility and mobility and how those two issues relate with the broader institutional settings in which pastoral production is embedded. We then apply this conceptual framework to an archaeological site also found in Gujarat, Bagasra, in order to explore probable dynamics of the ancient pastoral system in relation to resources accessibility and mobility. Dealing with archaeological past is always difficult given the limited availability of data. We argue that the conceptual approach proposed here allow us to draw some hypotheses about adaptation strategies, for which it appears a relevant way to further explore the dynamics of ancient pastoral systems.